ON/OFF domains shape receptive field structure in mouse visual cortex - Elaine Tring; Konnie K. Duan; Dario L. Ringach (Nature Communications, 2022)
Neurons in the early visual system respond preferentially to the onset or offset of light. Here the authors show that ON/OFF responses cluster in the mouse primary visual cortex, shaping the receptive fields of cortical cells.